Hubungan Antara Tingkat Stres Dengan Agresivitas Pada Caregiver Lansia - Putra, Dimas Prastia; Malay, Mohammad Nursalim; Setiawan, Nugroho Arief (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study originated from the idea that whether the level of stress has a relationship with the aggressiveness that will be experienced by the elderly caregiver. The purpose of this study was to determine the relationship between the level of stress and the agreement of the elderly caregiver. The population in this study was the people of the Sukabumi neighborhood II village with a total of 148 people. The sampling technique was simple random sampling and the samples in this study were 60 people. Data collection techniques in this study used a psychological scale including a stress scale and a scale of aggressiveness. Aggressiveness scale totaled 37 items (α = 0.925), on the stress scale amounted to 37 items (α = 0.874). The analysis technique used is the Pearson product moment correlation analysis technique which is assisted by the JASP version 0.14.1.0 program. The data analyzed showed the result, the correlation was r = 0.462 and the significance was p <0.001. So the results of the analysis show that there is a significant relationship between stress levels and aggressiveness in elderly caregivers, with the effective contribution of stress variables to the dependent variable by 21.4%, while the influence of other variables outside the study is 78.6%.Key words: stress, aggressiveness, elderly caregiver